GIS approach to estimate windbreak crop yield effects in Kansas-Nebraska - Osorio Morillo, Raul Jefferson (Kansas State University, 2017)
Windbreaks were originally promoted across the Great Plains region of the U.S to reduce wind erosion in general. A review paper published nearly 30 years ago showed yield increases for a variety of crops associated with windbreaks. However, with the widespread use of no-till systems in all farming and advanced crop genetics, the question is “Do windbreaks still provide a yield benefit?” This study compared multiple years of data from protected and unprotected fields across Kansas and few sites in Nebraska looking at relative crop yield differences of five crops: soybeans, wheat, corn, sorghum and sunflowers. Georeferenced data already existed, generated by automated combine yield monitors, and stored on farmer's computers. There were three sets of data collected for each field. The first level is general field level information, using aerial photography and on-site observations to measure the characteristics of the windbreak (length, height and density). The second was from the yield monitor; this data was analyzed with ArcGIS 10.3.1 to visualize windbreak interaction with crop yield. Multiple means comparisons (protected versus unprotected) through two sample T-tests were conducted to determine if the yield in protected areas of fields was significantly different from the yield in unprotected areas. The third data-layer is climate data that was factored into yield analysis to compare wet, normal and dry growing seasons through a Chi-Square 2x2 test analysis. Optical density of windbreaks from leaf-on/off ground-based photos was assessed using SigmaScan Pro 5.0 software as possibly an important factor influencing the windbreak effect. Finally, the yield loss was estimated from the windbreak footprint to see if yield increases are enough to compensate for the area taken out of crop production. Results showed that soybeans (81 crop/years) had the most positive response to windbreak effect with a yield increase 46% of the time, with a 16% average yield increase. Sorghum (31 crop/years) had the highest average yield increase with 25%. Narrow windbreaks (1 to 2 tree rows with an average of 52 ft. width) and those on the north edge of fields resulted in yield increases which compensated for the footprint of the windbreak more often than wider windbreaks on the south edges of fields. Significant yield increases were less than the decreases in the protected area. There was no evidence to show the windbreak effect on yield had any association with critical month precipitation for any crop or orientation group. According to the results obtained, modern hybrids and varieties are possibly less responsive to yield increases due to windbreak effect than older crop varieties. Future studies should collect more data from fields with different windbreak widths distributed more widely across the region to confirm these results. Overall, this project updated our knowledge of windbreak/crop yield interactions and may possibly influence their future role as a conservation practice in the Great Plains.
Keywords: Crop yield; Geographic information system (GIS); Kansas; Nebraska; Windbreak effects; Great Plains